Factors affecting pelvic rotation in idiopathic scoliosis: Analysis of 85 cases in a single center. Issue 46 (November 2016) - Zhao, Yunfei; Qi, Lin; Yang, Jun; Zhu, Xiaodong; Yang, Changwei; Li, Ming
Abstract : Abstract: Pelvic rotation (PR) is commonly seen in patients with idiopathic scoliosis (IS), but factors contributing to this phenomenon and its relationship with the surgical outcome are not well established. This retrospective study included 85 IS patients in 2 groups: thoracic curve dominance group (group A) and lumbar curve dominance group (group B). Pre- and postoperative PR was measured on standing posteroanterior radiographs by the left/right ratio (L/R ratio) of horizontal distance between the anterior superior iliac spine (ASIS) and the inferior ilium (SI) at the sacroiliac joint on the same side in both groups. Other radiographic data, age, sex, and Risser sign of each patient were recorded to analyze their correlations with PR before and after operation. The patients ranged in age from 10 to 35 years with a mean of 17.0 ± 5.2 years. The mean L/R ratio of PR before operation was 0.99 (0.73–1.40) versus 0.98 (0.87–1.26) after operation. The L/R ration was beyond the range of 1 ± 0.1 (indicating the presence of PR) in 17 (20%) patients before operation and in 14 (16.5%) patients after operation. There was no significant difference in PR between the 2 groups of patients either before ( P = 0.468) or after ( P = 0.944) surgery. The preoperative PR showed a very low correlation with Risser sign ( r = 0.220, P = 0.043), apex vertebral rotation (AVR) in the proximal thoracic curve ( r = 0.242, P = 0.026), and AVR in the lumbar curve ( r = 0.213, P = 0.049), while the postoperative PR showed a very low correlation with Risser sign ( r = −0.341, P = 0.001) and postoperative trunk shift (TS) ( r = −0.282, P = 0.009). Multiple stepwise regression analysis showed that preoperative PR was affected by proximal thoracic curve AVR and lumbar curve AVR. There was no significant difference between PR before operation and 2 years after operation. Preoperative PR was mainly correlated with Risser sign and the rotation status of the proximal thoracic curve and lumbar curve, while postoperative PR was mainly correlated with Risser sign and postoperative TS.